Implementasi Pengelolaan Kelas dalam Meningkatkan Efektivitas Pembelajaran Siswa di Kelas IV SD Negeri 0119 Banjar Raja - Suheddin Hasibuan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Based on the research results, it can be concluded that (1) Implementation of Classroom Management in Improving the Effectiveness of Student Learning in Class IV SD Negeri 0119 Banjar Raja has taken place effectively, and can increase the effectiveness of student learning. It can be known based on the teacher's strategy in preparing various things needed for the teaching and learning process, for example teaching media, learning tools, and preparation of lesson plans. Besides that, the teacher's strategy for opening lessons is by giving encouragement to their students' learning enthusiasm. (2) Factors supporting and inhibiting the implementation of classroom management in increasing the effectiveness of student learning in class IV SD Negeri 0119 Banjar Raja. These supporting elements include adequate infrastructure, qualified homeroom teachers and experts in their profession, strategic location, safe, surrounding environment clean classrooms, and the interaction of the homeroom teacher with the surrounding environment. The obstacle is the diversity of students' characteristics, such as the presence of students who fight, do not carry out pickets.